Leukemic transformation in myelodysplastic syndrome: A case report with review of risk factors (Indian Journal of Case Reports, 2019)
Myelodysplastic syndromes are a group of clonal disorders affecting the hemopoietic stem cells and characterized by peripheral cytopenias with normocellular to hypercellular bone marrow and various morphological abnormalities in one or more hemopoietic cell lines. MDS carries a high risk of progression to acute myeloid leukemia especially in subtypes with increased myeloblasts. Here, we present the case of leukemic transformation in MDSin a 41-year-old male who presented with complaints of generalized weakness, loss of appetite for 2 months and fever on and off for 1 week. The patient was diagnosed as MDS-multilineage dysplasia after blood examination and bone marrow biopsy but the patient refused for further treatment.